A case of contact‐lens‐related keratitis caused by fluoroquinolone‐ and tobramycin‐resistant Capnocytophaga sputigena. Issue 1 (February 2015) - Iimori, Hirohito; Suzuki, Takashi; Inoue, Tomoyuki; Mitani, Arisa; Miyamoto, Hitoshi; Ohkusu, Kiyofumi; Ohashi, Yuichi
Abstract : Introduction: Capnocytophaga species are rare keratitis‐causing pathogens. We herein report a case of keratitis caused by a drug‐resistant Capnocytophaga species in association with contact lenses. Case presentation: A 64‐year‐old female who wore a contact lens in her right eye to facilitate repair of the corneal epithelium complained of infection and discharge. Slit‐lamp biomicroscopy showed corneal abscessation and hypopyon. Thus, infectious keratitis was diagnosed. Direct microscopy and bacterial culture of a corneal scraping were performed. Because direct microscopy demonstrated the presence of Gram‐negative rods, we began treatment with topical 1.5 % levofloxacin and 0.3 % tobramycin every hour. The corneal infiltration increased 4 days after initiating the therapy. The culture report confirmed the presence of a Capnocytophaga species with fluoroquinolone and aminoglycoside resistance and susceptibility to cephalosporins and minocycline. We switched to topical 0.5 % cefmenoxime every hour and oral minocycline at 200 mg day −1 . The corneal inflammation subsided within 2 weeks. The bacterial isolate was identified as Capnocytophaga sputigena using 16S rRNA sequencing. Conclusions: We encountered a case of keratitis caused by C. sputigena with reduced fluoroquinolone and aminoglycoside susceptibility.